The Christmas trespassers [large type] - Fenady, Andrew J. (Wheeler large print western series., 2018)
"After losing his wife and children in the Civil War, Shad Parker moved to Texas and planted a DO NOT TRESPASS sign on his land and his heart. Enter three scrappy orphans hiding in a cave on Shad's land. Shad grudgingly saves their lives and takes them in. Then a gang of bank robbers shows up..."--Provided by publisher.